Natural variation of C‐repeat‐binding factor (CBFs) genes is a major cause of divergence in freezing tolerance among a group of Arabidopsis thaliana populations along the Yangtze River in China. Issue 4 (31st May 2013) - Kang, Juqing; Zhang, Huiting; Sun, Tianshu; Shi, Yihao; Wang, Jianqiao; Zhang, Baocai; Wang, Zhiheng; Zhou, Yihua; Gu, Hongya
Summary: We used a monophyletic group of four natural populations of Arabidopsis thaliana expanded from a single ancestor along the Yangtze River c . 90 000 yr ago to study the molecular mechanism of the divergence in their freezing tolerance, in order to gain an insight into the genetic basis of their local adaption to low temperatures. Freezing tolerance assays, measurements of metabolites in the raffinose biosynthesis pathway and transactivation‐activity assays of variation in forms of cold‐responsive transcription factors were conducted on the four populations. Quantitative trait locus mapping was adopted with F2 populations of the most‐ and least freezing‐tolerant populations. The degree of freezing tolerance among the four populations was negatively correlated with the lowest monthly average temperature of January in their native habitats, and positively correlated to the expression level of some cold‐regulated genes. We identified a major locus harboring three cold‐responsive transcription factor genes CBF1 – 3, and found a nucleotide insertion in CBF2 in all populations except SXcgx, which generated a dysfunctional CBF2 protein. The CBF2 in SXcgx experienced a stronger natural selection in the cooler environment after CBF3 lost its response to low temperature, which possibly reflects a local adaptation of these populations during the expansion from a common ancestor.